PENGARUH PERBANDINGAN MASSA TERHADAP SIFAT MEKANIK KOMPOSIT SANDWICH GLASS FIBER POLYURETAN FOAM CORE SEBAGAI MATERIAL UNTUK APLIKASI RUMAH KOMPOSIT TAHAN GEMPA - Al Wajdi, Habib Hussein; Hestiawan, Hendri; Rohman, Saeful (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2024)
Composite Houses at the BPPT material technology center and polymer technology center were designated as centers of superior polymer composite science and technology in 2018. For this reason, BPPT designed earthquake-resistant composite houses using lightweight materials so they are easy to carry and fast to install, namely using an easy knock down connection system. disassembled. This earthquake-resistant house uses composite materials, namely Styrofoam or polystyrene foam and glass fiber reinforced plastic (Fiberglass Reinforced Plastics / FRP). This material is stacked like a sandwich so it is called a sandwich composite panel. The weight of this panel is only about 2 kilograms, 30 percent lighter than cement walls reinforced with glass fiber or Fiberglass. The purpose of this study was to analyze the bending strength value of the Fiberglass fiber sandwich composite in the bending test and the results of the bending value of the Fiberglass fiber sandwich composite with the specification of an earthquake resistant composite house (RKTG) and the effect of matrix strength on the fiberglass fiber sandwich composite using polyurethane core with the hand lay-up technique.. It is said to be simple because the technique is very easy to apply, namely liquid resin is smeared over a mold and then the first layer of fiber is placed on top of it, then using a PVC resin spatula it is flattened again. This step is carried out continuously until the desired specimen thickness is obtained. Bending test values with each mass ratio of 1 kg, 1.5 kg, 2 kg, and 2.5 kg. It can be concluded that from the results of this research at a mass ratio of 1.5 kg the results are 2,242 MPa, from the results of this research the Ultimate value Higher Tensile Strength compared to other masses.